1988
DOI: 10.1007/bf03259890
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Organophosphate Poisoning

Abstract: Many organophosphate compounds are pesticides widely used for the control of insect vectors. They are not ideal agents because they lack target vector selectivity, and have caused severe toxicity and even death in humans and domestic animals. Their toxicity has been recognised since the 1930s, when they were also developed for use as chemical warfare agents. The mechanism of action of organophosphates has been determined in some depth; the understanding of the toxic effects resulting from the inhibition of cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 67 publications
0
73
0
1
Order By: Relevance
“…2 The environmental protection agency of the United States estimated that 3,000 hospitalizations per year were for insecticide poisoning with a fatality rate of 50% in the paediatric age group and 10% in adult. 6 OPC poisoning is a common medical emergency in Bangladesh. Begum et al in their study carried out in four hospitals of Chittagong division observed OPC poisoning as leading cause of morbidity and mortality due to poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…2 The environmental protection agency of the United States estimated that 3,000 hospitalizations per year were for insecticide poisoning with a fatality rate of 50% in the paediatric age group and 10% in adult. 6 OPC poisoning is a common medical emergency in Bangladesh. Begum et al in their study carried out in four hospitals of Chittagong division observed OPC poisoning as leading cause of morbidity and mortality due to poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…The active site hydroxyl group of the catalytic serine residue of serine hydrolases is often the target of various compounds that covalently modify it resulting in the loss of enzymatic activity [13,19]. The compounds, thus acting as pseudosubstrates, react with the enzyme but unlike the normal carboxylester substrates, the pseudosubstrates are not converted to products.…”
Section: Inhibition Of Purified Pmpmease By Serine Hydrolase Inhibitorsmentioning
confidence: 99%
“…Their toxicities has been received equal importance and based on these properties the chemical warfare agents are developed [3]. In the last 50 years different OPC has been synthesized and marketed [4,5].…”
Section: Discussionmentioning
confidence: 99%